Decode-and-Forward vs. Amplify-and-Forward Scheme in Physical Layer Security for Wireless Relay Beamforming Networks - Tuan, Nguyen Nhu (Journal of Science and Technology on Information security, 2020)
Abstract— To secure communication from the sender to the receiver in wireless networks, cryptographic algorithms are usually used to encrypt data at the upper layers of a multi-tiered transmission model. Another emerging trend in the security of data transmitted over wireless networks is the physical layer security based on beamforming and interference fading communication technology and not using cryptographic algorithms. This trend has attracted increasing concerns from both academia and industry. This paper addresses how physical layer security can protect secret data compare with the traditional cryptographic encryption and which is the better cooperative relaying scheme with the state of the art approached methods in wireless relaying beamforming network. Tóm tắt— Việc bảo mật truyền thông vô tuyến từ nơi gửi đến nơi nhận thường sử dụng các thuật toán mật mã để mã hoá dữ liệu tại các tầng phía trên trong mô hình phân lớp. Một xu hướng khác đang được quan tâm rộng rãi là bảo mật tầng vật lý dựa trên kỹ thuật truyền tin beamforming và kỹ thuật tương tác fading kênh chủ động. Xu hướng này hiện đang được thu hút cả trong giới công nghiệp và nghiên cứu. Đóng góp của bài báo này là làm rõ khả năng bảo mật tầng vật lý và so sách chúng với phương pháp bảo mật dùng kỹ thuật mật mã truyền thống. Bài báo cũng so sánh hai kỹ thuật chuyển tiếp được sử dụng chính trong bảo mật tầng vật lý cho mạng vô tuyến chuyển tiếp là Amplify-and-Forward và Decode-and-Forward.